The Implementation of Simple, Fast, Low Cost Judicial Basis In the Judicial Practices - Yuhelson Yuhelson (Ideas Publishing, 2018)
The basic problems judgments simple, fast and low cost also upon the Supreme Court, where various rules, whether in the form of the Supreme Court rules or circular Letter of the Supreme Court was issued in order to accelerate the examination process until the escaping minutasi decision so that the person can immediately determine further steps, including by utilizing technology to speed up the process. But until this time, in the jurisdiction of the criminal justice not mistakes to make small summary court and not teradopsi in total on the basis of restorative justice. Although there is a process of checking with the event quickly in KUHAP only against criminal acts of light and the matter in a traffic accident (laka necessarily) and adopted the basis of restorative justice on the legislation that are custom without connecting with KUHAP. The basis of the judiciary is simple, fast and low cost in the jurisdiction of the practice of the law appears in the form of a distorted, where often a suspects/Defendants start since the jurisdiction of the pre-adjudikasi offered not to use mentoring from the power of the Law with the reasons will be changed the article will tangled by so that the requirement will be more lightly.